Efficiency study of Greek health units of the public sector using data envelopment analysis method, before and during the start of the economic crisis - Georgios I. Farantos; Nikitas Spiros Koutsoukis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - The purpose of this paper is to investigate the Technical Efficiency through an Efficiency Study of Health Units of the Greek Ministry of Health, before and during the start of the Economic Crisis in Greece. Design/methodology/approach - The research has been designed to collect data regarding the Health Units of the Public Sector from the Greek Statistical Authority (ELSTAT) and to process that data with the use of the Data Envelopment Analysis software. The methodology of the research extends to the application of the Efficiency Study of Decision Making Units (DMUs), the study of variations of Technical Efficiency during a number of years and the extraction of conclusions regarding variations in Technical Efficiency at a time period before and during the start of the Crisis. Data from large Health Units was used in order to achieve comparison of the results. Findings - We calculate the DEA scores based on the most common DEA models (CCR, BCC and Super Efficiency) for the Health Units of the Greek Ministry of Health. We examine the variation in Technical Efficiency of the Health Units during the extent of the time period of the study. The Efficiency Study of the Health Units leads to useful conclusions regarding the variation in the observed Efficiency of the Units and the integration of the Efficiency variation studies, as part of the initial stage of an Integrated Crisis Management. The research ranks the efficient and non-efficient units and suggests ways of improvement. Research limitations/implications - This is a study about the Health Units of the Public Sector using size as a criterion. The investigation is limited to the Public Health Sector and its conclusions cannot be extended to the Private Health Sector. There are no geographical restrictions. Originality/value - This is an innovative research which allows for further case studies in the future and completion of Efficiency studies after the end of the Economic Crisis.
Keywords: C60; I1; H12; 330; Economic Crisis; Data Envelopment Analysis; Efficiency Study; Decision Making Unit; Health Units